Tumor microenvironment in spontaneously occuring tumors and in vitro evaluation of hypoxia associated mutagenesis - Trncic, Nadira, author; LaRue, Susan M., advisor (Colorado State University. Libraries, 2008)
The importance of the tumor oxygenation status in tumor progression and tumor response to radiation and other forms of treatment has been investigated in many experimental and clinical studies. Oxygen status can impact cell killing associated with radiation treatment and, interestingly radiation can also impact subsequent oxygen levels. Part I of my dissertation is concerned with this phenomenon of reoxygenation. A multiparameter study was conducted in naturally occurring canine tumors to evaluate physiological changes in the tumor microenvironment following a 3 Gy fraction of radiation. Pre-treatment values of partial pressure of oxygen, interstitial fluid pressure, microvascular perfusion, level of apoptosis, and microvessel density were compared to the 24 hours post-radiation measurements in the same location. I analyzed changes in all parameters and evaluated the relationship between parameters and pO2. In disagreement with my working hypothesis, I only found inverse correlation between changes in oxygen level and changes in IFP. In Part II, I used the CHO AL mutation assay to investigate the role of hypoxia alone in the induction of mutagenesis. After exposing cells to different hypoxic conditions I found that only severe hypoxia can cause mutations in human-hamster hybrid cells (AL). Level of oxygen that induced mutations was less than 0.63 mm Hg. Both the complement-mediated AL mutation assay and the flow cytometry mutation assay were done. Mutant cells were sorted from the mutant peak, and the clonal populations of cells were analyzed with the AL flow cytometry assay to determine if cells were really mutated (negative for CD59) and not just downregulated in hypoxia. Quantitative analysis of mutations that were performed did not detect any changes in the CD59 gene. Tumor reoxygenation, as shown here, may not be associated with improved tumor perfusion, but rather with other factors such as decreased oxygen consumption. These studies proved that severe hypoxia can cause mutations and possibly tumor genetic instability, and that those levels of oxygenation can be found in spontaneous tumors in dogs, which are a great tumor model for translating findings to human cancers.
Keywords: cancer; hypoxia; mutagenesis; reoxygenation; spontaneous tumors; tumor microenvironment; medical imaging; medicine; oncology